COMPONENTS OF FORMATION OF LEXICAL SKILLS IN LANGUAGE LEARNING (Conferencea, 2023)
This article provides theoretical knowledge about the components of formation of lexical skills in linguistics students. Receptive and productive lexical skills are thoroughly explained.